2016
DOI: 10.3390/rs8110887
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-Induced Building Damage Detection with Post-Event Sub-Meter VHR TerraSAR-X Staring Spotlight Imagery

Abstract: Abstract:Compared with optical sensors, Synthetic Aperture Radar (SAR) can provide important damage information due to its ability to map areas affected by earthquakes independently from weather conditions and solar illumination. In 2013, a new TerraSAR-X mode named staring spotlight (ST), whose azimuth resolution was improved to 0.24 m, was introduced for various applications. This data source made it possible to extract detailed information from individual buildings. In this paper, we present a new concept f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…2020, 9, 238 2 of 16 improved [8,9]. Remote sensing images can be acquired quickly and can reflect the objective world comprehensively and intuitively, and they provide a new information source for the rapid recognition and assessment of earthquake damage [10,11]. There is a lot of research about disaster risk assessment based on remote sensing images.…”
Section: Introductionmentioning
confidence: 99%
“…2020, 9, 238 2 of 16 improved [8,9]. Remote sensing images can be acquired quickly and can reflect the objective world comprehensively and intuitively, and they provide a new information source for the rapid recognition and assessment of earthquake damage [10,11]. There is a lot of research about disaster risk assessment based on remote sensing images.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggest that texture information performs better for classifying collapsed buildings. Similar works use high-resolution SAR data, such as ALOS-2 PALSAR-2 in the case of the 2015 Nepal earthquake and TerraSAR-X datasets for the 2008 Wenchuan earthquake, to derive geometric and texture features, and evaluate several classic machine learning algorithms to classify damaged buildings from post-event remote sensing data [12,13]. On the other hand, frameworks that integrate pre-event vector information and post-event VHR remote sensing data together with advanced machine learning technologies have been proposed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of algorithms and parameters were tested on post-event aerial imagery for the earthquake in Christchurch, New Zealand, and the results showed that object-based approaches can produce better results than pixel-based approaches in earthquake damage detection using remotely sensed images [32]. Random forest (RF), SVM, and K-nearest neighbor (K-NN) classifiers were applied to classify collapsed and standing buildings with the post-event SAR image and the building footprint map [33].…”
Section: Introductionmentioning
confidence: 99%